Forensic Accounting as Antibiotic for Pressing Corruption Infection in Indonesia - Ghusti Ayu Criestiant Rolihlahla; Made Dudy Satyawan; Ni Nyoman Alit Triani (Journal of Economics, Business, and Accountancy Ventura, 2017)
Effectiveness of corruption cases aimed at making the corrupt severely punished in a court of corruption and bring the deterrent effect for public officials who intend to engage in corruption. This study aims to explain the depth of the role of forensic accounting as well as how it applied in the handling and disclosure of corruption cases in Indonesia. The hope of forensic accounting can be accepted and applied by all auditors general inspectorate at the ministry/government agencies at both central and local levels, so that corruption can be detected early on using the science of forensic accounting. This study uses a qualitative methodology with an interpretive approach, with key informants from the Directorate Investigator and Special Economic Crime, the Criminal Investigation Police, KPK, as well as the Financial and Development Supervisory Agency. The result of this study indicates that the forensic accounting interpreted as potent antibiotics to suppress the rampant corruption in Indonesia. Investigation method often used investigator/auditor using forensic accounting knowledge to produce valid evidence in court corruption, including documentary evidence of the state audit the calculation of financial loss and statement of experts (auditors) in the corruption trial.